The analysis of specialists’ opinion on the implementation of concept of risk management in clinical trials of drugs - Zupanets, E. A.; Dobrova, V. Ye. (Zaporozhye Medical Journal, 2016)
At the modern stage of the pharmaceutical industry development quality risk management becomes an integral part of all the processes of drug development and clinical trials (CT). Aim of paper is to study the opinion of competent experts in the field of CT of drugs and formation of strategic ways of risk management at the clinical site as well as to identify possible complications in the practical implementation of these approaches. Materials and methods: the survey of the expert group (17 people) to select the indicators and the parameters measuring the risks of CT at clinical site, as well as their acceptable levels. The assessment of survey results was done using non-parametric statistics methods. Results of research. There were established the differences of various stakeholders’ notion of conceptual content and practical importance of quality management and the application of risk-oriented approaches at the clinical site in relation to CT quality that can become an obstacle to their implementation. The introduction of risk-based monitoring into the system for CT management at the clinical site corresponds to the interests of all stakeholders involved in the study. General concernment of the customer’s representatives, regulatory authority and researchers should be an important basis for the implementation of the risk-based management at the clinical site. So, it is necessary to create a common understanding of the terminology, objectives and expected outcomes of risk management at the clinical site, as well as a clear allocation of the duties and responsibilities of each side. Conclusions. The expediency of the concept of risk management application at the clinical site, practical orientation, as well as the need to develop scientific and methodological approaches for its implementation, contributing to the formation of a common basis for action and coordinated interaction of stakeholders involved in the management of CT were proved.